Vaccination status of individuals with diabetes mellitus treated in Primary Healthcare: a cross-sectional study - Francisco João de Carvalho Neto; Luisa Helena de Oliveira Lima; Mônica Antar Gamba; Rosilane Lima de Brito; Lucilane Maria Sales da Silva; Ana Roberta Vilarouca da Silva (Revista Latino-Americana de Enfermagem)
Objective to analyze the vaccination status of individuals with type 1 and type 2 diabetes in Primary Healthcare. Method cross-sectional, analytical study conducted in 25 Family Health teams with 274 individuals with diabetes. Sociodemographic and clinical variables were evaluated, as well as the full vaccination schedule for each vaccine recommended by the National Immunization Program, through bivariate analysis and logistic regression. Results among individuals with diabetes mellitus, the following incomplete vaccination rates were found: 69.1% for hepatitis B; 64.6% for diphtheria and tetanus; 74.3% for yellow fever; 87.9% for pneumococcus; 87.9% for varicella; 24.5% for influenza; and 0.7% for COVID-19. The reported reasons for low vaccination rates included not knowing the importance of vaccination and not being informed by healthcare providers. A statistically significant association was found between sociodemographic and clinical profile regarding the full vaccination schedule between the influenza vaccine and age and income; COVID-19 and age, type of diabetes and duration of diabetes. Conclusion individuals with type 1 and type 2 diabetes treated in Primary Healthcare showed low vaccination rates, which is concerning due to increased vulnerability to vaccine-preventable infections and mortality within this group.